Quantitative analysis of quaternary mixtures in topical creams using cutting-edge HPLC technique: environmental impact and sigma methodology - Maha A. Alwaili; Osama A. Mahmoud; Samar M. Mahgoub; Manal A. Almalki; Hassan A. Rudayni; Ahmed A. Allam; Mustafa Ahmed Abdel-Reheim; Osama A. Mohammed; Mahmoud A. Mohamed (Green Chemistry Letters and Reviews)
Benzyl Nicotine (BN) and etofenamate (ETO), when combined with methylparaben (MP) or benzyl alcohol (BA), are highly effective for treating muscle and joint pain. This study presents a newly developed and verified RP-HPLC method for measuring ETO and BN in the presence of MP or BA in their dosage forms. The approach utilizes eight environmentally friendly tools and the BAGI white tool to assess their eco-friendliness and effectiveness. The method uses a photodiode array PDA detector at 254 nm and symmetry column (C18, 150 mm × 4.6 mm, 5μm) in an isocratic process with a mobile phase of 0.1% orthophosphoric acid and methanol in a (45:55, v/v) adjusted pH 6.5 with 0.2% triethylamine solution at a flow rate of 1.5 mL/min, separation was accomplished in RP-HPLC. The calibration curves exhibited linearity across the concentration levels specified in the approach. Therefore, the procedure has been effectively applied in laboratory evaluation for medications in the presence of MP or BA, showcasing the exceptional selectivity of this strategy. The recommended approach was executed using the Six Sigma methodology, resulting in a Cpk value greater than 1.33. The procedures were successfully validated based on the ICH standards.